Luminescence efficiency improving method and packaging method of narrow-band fluoride fluorescent powder

By rigorously selecting high-purity raw materials, optimizing doping concentration and process parameters, and combining orthogonal experimental design and heat treatment, the problem of low luminous efficiency of narrow-band fluoride phosphors has been solved, achieving high-efficiency and stable luminous performance suitable for high-end LED lighting and displays.

CN120843089APending Publication Date: 2025-10-28XUYU OPTOELECTRONICSSHENZHEN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510960083.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

The low luminous efficiency of existing narrowband fluoride phosphors is mainly due to the lack of systematic optimization in the selection of dopant and charge compensator ratios, improper control of material impurities, resulting in insufficient activation efficiency of luminescent centers, high non-radiative losses, and poor crystal structure and defect state distribution.

Method used

By rigorously screening high-purity matrix materials and dopants, and using orthogonal experimental design to determine the doping concentration range, combined with heat treatment under a reducing atmosphere and fine crushing and sieving, the doping system and process parameters are optimized to ensure the synergistic relationship between dopants and charge compensators, thereby improving the quantum efficiency and color purity of the material.

Benefits of technology

It significantly improves the luminous efficiency and thermal stability of narrowband fluoride phosphors, achieves high color purity and batch consistency, meets the light and color performance requirements of high-end LED lighting and displays, and enhances the market competitiveness of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120843089A_ABST
    Figure CN120843089A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fluorescent powder, provides a luminous efficiency improving method and a packaging method of narrow-band fluoride fluorescent powder, and solves the problem of low luminous efficiency of the existing narrow-band fluoride fluorescent powder in the prior art. The method comprises the following steps: screening an initial raw material according to a preset purity requirement to obtain a target raw material, and obtaining target doping concentrations of a dopant and a charge compensation agent according to an orthogonal test method and a preset doping concentration range; performing mixing treatment on the target raw materials according to the target doping proportion to obtain a uniformly mixed premix; performing heat treatment on the premix in a reducing atmosphere according to a preset temperature range to obtain a heat-treated material; and crushing and screening the heat-treated material to obtain the narrow-band fluoride fluorescent powder. The invention has excellent photo-thermal stability and long-term reliability, and is suitable for wide-color-gamut high-color-rendering LED illumination, high-brightness display backlight and high-power illumination application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of phosphors, and more particularly to a method for improving the luminous efficiency of narrow-band fluoride phosphors and an encapsulation method. Background Technology

[0002] Narrow-band fluoride phosphors, due to their excellent color purity, good thermal stability, and low self-absorption loss, have been widely used in full-spectrum LED lighting and display applications. Especially... and Red fluoride phosphors with Mn and Yb ions as the matrix exhibit significant advantages in wide color gamut and high color rendering LED products due to their narrow emission band and precise color coordinates.

[0003] However, in the actual preparation and application of narrowband fluoride phosphors, the following prominent problems still exist in the current technology: On the one hand, the selection of the ratio of dopants and charge compensators lacks systematic optimization and often relies on experience or single-factor experiments, making it difficult to fully explore the synergistic effect of multiple parameters, resulting in insufficient activation efficiency of the material's luminescent centers and high non-radiative loss. On the other hand, each step, such as the control of raw material impurities, uniform powder mixing, and heat treatment processes, has a significant impact on the final crystal structure and defect state distribution. If not handled properly, impurity phases, lattice distortion, and surface defects can easily form, further reducing luminescence efficiency. Summary of the Invention

[0004] In view of this, embodiments of the present invention provide a narrow-band fluoride phosphor and a method for preparing the same, in order to solve the problem of low luminous efficiency of existing narrow-band fluoride phosphors in the prior art.

[0005] In a first aspect, embodiments of the present invention provide a method for improving the luminous efficiency of narrowband fluoride phosphors, the method comprising: The initial raw materials are screened according to the preset purity requirements to obtain the target raw materials. The target raw materials include matrix materials, dopants and charge compensators. The matrix materials include SrF2 and CaF2, the dopants include MnF3 and YbF3, and the charge compensator includes LiF. Based on orthogonal experimental design and preset doping concentration ranges, the target doping concentrations of the dopant and charge compensator were obtained. Specifically, the preset doping concentration range for MnF3 was 0.5–2.0 mol%, for YbF3 it was 1.0–3.0 mol%, and for LiF it was 0.8–1.5 mol%. The target raw materials are mixed according to the target doping ratio to obtain a uniformly mixed premix. The premixed material is heat-treated in a reducing atmosphere according to a preset temperature range to obtain a heat-treated material. The heat-treated material is crushed and sieved to obtain the narrow-band fluoride phosphor.

[0006] Preferably, obtaining the target doping concentrations of the dopant and charge compensator based on orthogonal experimental design and a preset doping concentration range includes: Based on the preset doping concentration ranges of the dopant and the charge compensation agent, multiple concentration levels are selected and combined to obtain an orthogonal experimental factor table; Based on the orthogonal experimental factor table, obtain multiple sets of experimental formulations to be prepared; The phosphor was prepared according to the preset preparation parameters and the experimental formulation group to obtain the corresponding phosphor samples; The performance of each phosphor sample was tested to obtain the luminescence performance parameters of each phosphor sample. Correlation analysis was performed on the luminescence performance parameters and experimental formulations corresponding to each phosphor sample to obtain the target doping concentrations of dopants and charge compensators.

[0007] Preferably, the step of selecting multiple sets of doping concentration levels according to the preset doping concentration ranges of the dopant and the charge compensator to obtain an orthogonal experimental factor table includes: Based on the preset doping concentration range of the dopant and the charge compensator, the concentration range is segmented to obtain the effective concentration range of the dopant and the charge compensator; Concentration sensitivity is evaluated based on the effective concentration range to obtain the high-sensitivity and low-sensitivity segments of the dopant and the charge compensator; The high-sensitivity region is divided into non-equidistant sections and the low-sensitivity region is divided into equidistant sections to obtain a set of concentration levels for the dopant and the charge compensator. The theoretical energy transfer efficiency is calculated for each set of concentration levels to obtain the energy co-efficiency parameter of each set of concentration levels. The energy synergy efficiency parameters are filtered according to a preset threshold to obtain an effective concentration level combination that meets the preset energy transfer requirements; Based on the effective concentration level combination and the preset orthogonal experimental table type, obtain the orthogonal experimental factor table.

[0008] Preferably, the step of performing correlation analysis between the luminescence performance parameters and experimental formulation groups corresponding to each phosphor sample to obtain the target doping concentrations of the dopant and charge compensator includes: The luminescence performance parameters of each phosphor sample are normalized according to a preset weight to obtain a weighted score of the experimental formulation corresponding to each phosphor sample. The luminescence performance parameters include luminescence efficiency, full width at half maximum (FWHM), and thermal stability. Based on the weighted score and the preset score threshold, all experimental formulas are screened to obtain a group of candidate experimental formulas with a weighted score higher than the threshold. Based on the concentration levels of each dopant in the candidate experimental formulation group, the weighted average score corresponding to each dopant concentration level is calculated to obtain the main effect weighted score distribution of different dopant concentration levels; Based on the concentration levels of each charge compensator in the candidate experimental formulation group, the weighted average score corresponding to each charge compensator concentration level was calculated to obtain the main effect weighted score distribution of charge compensator at different concentration levels. Based on the main effect weighted score distribution of dopant and charge compensator, the concentration ranges with the most significant increase in weighted score for dopant and charge compensator are determined and denoted as the main effect concentration ranges. Based on the main effect concentration range and the concentration combination of dopant and charge compensator in the candidate experimental formulation group and their weighted scores, interaction analysis was performed to obtain the interaction analysis results. Based on the interaction analysis results, the target doping concentrations of the dopant and charge compensator are obtained.

[0009] Preferably, the interaction analysis is performed based on the main effect concentration range and the concentration combinations of dopants and charge compensators in the candidate experimental formulation group, along with their weighted scores, to obtain the interaction analysis results, including: Based on the dopant and charge compensator concentration combinations of the candidate experimental formulations, grouping is performed within the main effect concentration range to obtain combined groupings with dopant concentration levels as rows and charge compensator concentration levels as columns; Based on the above combination grouping, the weighted score dataset corresponding to each combination of dopant concentration level and charge compensator concentration level is obtained; Based on the weighted scoring dataset, the average weighted score corresponding to each combination of dopant and charge compensator concentrations is calculated to obtain the average weighted score matrix of each combination. Based on the single-factor average weighted score distribution corresponding to each dopant concentration level in the candidate experimental formulation group, and the single-factor average weighted score distribution corresponding to each charge compensator concentration level, a comparative processing was performed to obtain the scoring reference benchmark. The interaction analysis matrix of each dopant and charge compensator concentration combination is obtained by comparing the scoring reference benchmark with the average weighted scoring matrix of each combination. The significance of the interaction analysis is determined based on the interaction analysis matrix and the scoring reference, and the interaction analysis results are obtained.

[0010] Preferably, the step of heat-treating the premixed material under a reducing atmosphere within a preset temperature range to obtain a heat-treated material includes: According to a preset reducing atmosphere, the premixed material is heated to a target temperature according to a preset heating rate. The reducing atmosphere is a mixed gas including hydrogen and argon, wherein the mixing ratio of argon and hydrogen in the mixed gas is 95:5, and the target temperature is between 1100℃ and 1300℃. According to the vapor deposition method, the vapor phase component is deposited at the target temperature, and a lattice-oriented crystallization reaction occurs. The deposition reaction is maintained at a temperature and reducing atmosphere for a preset holding time to form fluoride crystal particles with a target average specific surface area. The preset holding time is 2-4 hours, and the target average specific surface area is 3 μm. 2 / g~5m 2 Between / g; The fluoride crystal particles are cooled to room temperature according to a preset cooling rate to obtain the heat-treated material, wherein the preset cooling rate is less than or equal to 2°C / min.

[0011] Preferably, the step of crushing and sieving the heat-treated material to obtain the narrow-band fluoride phosphor includes: The heat-treated material is placed in a planetary ball mill and crushed by ball milling according to a preset rotation speed and preset ball milling time to obtain pulverized material. The pulverized material is sieved according to the target particle size range to obtain the narrow-band fluoride phosphor. The preset rotation speed is 300 rpm, the preset ball milling time is 2 h, and the target particle size distribution range is 8~12 μm.

[0012] Preferably, after sieving the pulverized material according to the target particle size range to obtain the narrow-band fluoride phosphor, the method further includes: Tetraethoxysilane was used as a precursor and dissolved and mixed in ethanol:deionized water:ammonia water at a volume ratio of 4:1:0.1. The mixture was then subjected to a hydrolysis reaction to obtain a stable silica sol. The narrow-band fluoride phosphor is uniformly dispersed in the silica sol by ultrasonic vibration or mechanical stirring to form a phosphor suspension; The phosphor suspension is heated to 60°C and kept at a constant temperature for 2 hours to generate a silica coating layer with an average thickness of a preset value on the phosphor surface in situ by tetraethoxysilane. The product after the reaction was washed and dried to obtain a surface coating. Narrow-band fluoride phosphor in layers.

[0013] Secondly, embodiments of the present invention also provide a method for encapsulating narrow-band fluoride phosphors, characterized in that the narrow-band fluoride phosphors are obtained by the method described in the first aspect, the method comprising: The target refractive index is obtained based on the refractive index of the narrow-band fluoride phosphor, wherein the target refractive index is between 1.6 and 1.7. The corresponding encapsulating adhesive is obtained based on the target refractive index; According to the Yb in the narrow-band fluoride phosphor 3+ The absorption peak is used to obtain the target excitation wavelength; Based on the target excitation wavelength, obtain the corresponding blue LED light-emitting chip as the excitation light source; Based on the encapsulating adhesive and the blue LED light-emitting chip, a narrow-band fluoride phosphor is encapsulated to obtain the target light-emitting device.

[0014] Preferably, the encapsulation of narrow-band fluoride phosphors with the encapsulating adhesive and the excitation light source to obtain the target light-emitting device includes: A blue LED light-emitting chip is fixed on a pad on a chip carrier, wherein the chip carrier is provided with a copper-based heat sink; According to the preset ratio, the encapsulating adhesive and narrow-band fluoride phosphor are mixed to obtain phosphor colloid; The target light-emitting device is obtained by coating a blue LED chip with phosphor colloid and then curing it.

[0015] In summary, the beneficial effects of the present invention are as follows: This invention provides a method for improving the luminescence efficiency of narrow-band fluoride phosphors, systematically enhancing phosphor performance from multiple dimensions, including raw material purity, doping system optimization, and process parameter control. First, rigorous screening of high-purity matrix materials and dopants significantly reduces the interference of impurities on crystal growth and energy level structure, effectively suppressing non-radiative losses and providing a solid foundation for efficient luminescence. Second, optimization using orthogonal experimental design combined with a defined doping concentration range allows for a systematic exploration of the synergistic relationship between dopants and charge compensators, achieving optimal luminescent center distribution, significantly improving the material's quantum efficiency and color purity, and avoiding the quenching effect caused by high-concentration doping and the problem of insufficient luminescent centers at low concentrations. The heat treatment step, through precise control of temperature and reducing atmosphere, ensures the stability of the dopant ion valence state and the complete growth of the crystal lattice, further optimizing the phosphor's crystallinity and particle size distribution, reducing lattice defects and surface inhomogeneities, thereby enhancing photon absorption and emission efficiency. After meticulous crushing and sieving, the narrow-band fluoride phosphor obtained by this invention not only has high luminous efficiency, high color purity, and good thermal stability, but also excellent batch consistency and process adaptability. It can meet the stringent requirements for light and color performance and reliability in high-end LED lighting, display and other fields, and greatly enhance the market competitiveness of related products. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the embodiments of the present invention will be briefly introduced below. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, and these are all within the protection scope of the present invention.

[0017] Figure 1 This is a schematic flowchart of a method for improving the luminous efficiency of narrowband fluoride phosphors according to an embodiment of the present invention.

[0018] Figure 2 This is a schematic flowchart of a method for encapsulating narrowband fluoride phosphors according to an embodiment of the present invention.

[0019] Figure 3 This is a measured emission spectrum of an LED package prepared using narrow-band fluoride phosphor according to an embodiment of the present invention.

[0020] Figure 4 This is a diagram showing the chromaticity coordinates of the LED package prepared with narrow-band fluoride phosphor according to an embodiment of the present invention as the points of the ellipse in ANSI-4000K. Detailed Implementation

[0021] The features and exemplary embodiments of various aspects of the present invention will now be described in detail. To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be practiced without some of these specific details. The following description of the embodiments is merely intended to provide a better understanding of the present invention by illustrating examples of the invention.

[0022] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising..." does not exclude the presence of additional identical elements in the process, method, article, or apparatus that includes said element.

[0023] Example 1 See Figure 1 This invention provides a method for improving the luminous efficiency of narrowband fluoride phosphors, the method comprising: S1. Screen the initial raw materials according to the preset purity requirements to obtain the target raw materials, wherein the target raw materials include matrix materials, dopants and charge compensators, the matrix materials include SrF2 and CaF2, the dopants include MnF3 and YbF3, and the charge compensator includes LiF; Specifically, the target raw materials refer to all basic components that have undergone rigorous screening and meet high purity requirements, including matrix materials, dopants, and charge compensators. Matrix materials mainly include SrF2 and CaF2, dopants include MnF3 (manganese trifluoride) and YbF3 (ytterbium trifluoride), and the charge compensator is LiF (lithium fluoride). "High purity requirements" typically refer to a metal impurity content of less than 10 ppm to ensure the crystal integrity and luminescent performance of the final phosphor.

[0024] The purpose of this step is to control the purity and composition accuracy of the materials from the source. Inaccurate dopant and compensator impurities or compositions can lead to crystal growth defects or energy level structure distortions, severely impacting fluorescence efficiency and stability. Therefore, rigorous screening can minimize irrelevant impurities and optimize the doping environment, laying the foundation for subsequent high-performance narrowband luminescence.

[0025] In practice, inductively coupled plasma mass spectrometry (ICP-MS) is typically used to test the purity of raw materials. By analyzing batch test reports provided by suppliers and conducting on-site sampling, the purity of raw materials is confirmed batch by batch to meet requirements. Unqualified batches are directly rejected or returned. This high-standard raw material screening significantly reduces non-radiative energy levels caused by ineffective impurities, improves the yield and material consistency of subsequent processes, and creates the prerequisites for high-efficiency luminescence.

[0026] It is worth emphasizing that the selection of MnF3 and YbF3 as dopant precursors aims to directly introduce tetravalent manganese and trivalent ytterbium ions, which are crucial for achieving narrowband high-efficiency luminescence. If low-valence impurities such as divalent manganese or divalent ytterbium are present in the initial raw materials, non-radiative losses will significantly increase in subsequent processes, reducing luminescence efficiency. Therefore, when raw material batches are received, not only must the content of metal impurities be tested, but also valence state detection (such as XPS and XANES analysis) or stoichiometry must be used to ensure the proportion of high-valence dopant ions, guaranteeing the presence of Mn in the final system. 4+ and Yb 3+ Each plays a dominant role, providing a fundamental guarantee for high color purity and high-efficiency luminescence.

[0027] In practice, inductively coupled plasma mass spectrometry (ICP-MS) is typically used to detect the purity of raw materials, combined with valence state verification methods, to ensure that all raw materials meet design standards. Unqualified raw materials are strictly rejected or replaced to ensure that each batch of phosphor products has excellent yield, material consistency, and high luminescence performance.

[0028] S2. Based on the orthogonal experimental design and the preset doping concentration range, obtain the target doping concentrations of the dopant and charge compensator. Specifically, the preset doping concentration range for MnF3 is 0.5-2.0 mol%, for YbF3 it is 1.0-3.0 mol%, and for LiF it is 0.8-1.5 mol%. The target doping concentration of dopants and charge compensators refers to the optimal doping ratio that maximizes luminescence efficiency while ensuring fluorescence performance and material stability. Orthogonal experimental design is a commonly used multi-factor, multi-level parameter screening method that can efficiently identify the optimal concentration range.

[0029] In one embodiment, the present invention sets the doping concentration range of MnF3 to 0.5–2.0 mol%, the doping concentration range of YbF3 to 1.0–3.0 mol%, and the doping concentration range of LiF to 0.8–1.5 mol%. This range setting is mainly based on the following considerations: First, dopants (such as , The concentrations of doping agents and charge compensators (such as LiF) have a crucial impact on the luminescence efficiency, color purity, and thermal stability of fluoride phosphors. Too low a doping concentration may result in insufficient luminescent centers and weak luminescence intensity; while too high a doping concentration can easily induce concentration quenching, lattice distortion, or even impurity phase formation, leading to a decrease in luminescence efficiency. Therefore, by setting a scientifically reasonable concentration range, a balance between luminescence performance and material stability can be achieved to the greatest extent possible.

[0030] Secondly, the selected concentration range fully covers the literature reports and actual process window, which not only ensures theoretical feasibility, but also facilitates subsequent multi-factor and multi-level combined experiments through orthogonal experimental design to systematically explore the synergistic relationship between different factors, thereby screening out the optimal dopant and compensator ratio.

[0031] Finally, this range setting also allows for the adjustability of actual production processes, facilitating precise control of process parameters and quality consistency management during scale-up preparation. By combining orthogonal experimental design with the aforementioned preset concentration ranges, the optimal concentrations of target dopants and charge compensators with the best luminescence efficiency and most stable material properties can be efficiently and systematically identified, significantly improving the overall performance of narrowband fluoride phosphors.

[0032] The purpose of this step is to systematically and scientifically determine the optimal combination of dopant and compensator, avoiding inefficiency and resource waste caused by relying solely on experience or blind experimentation. By weighting and statistically analyzing multiple objective parameters (such as luminous efficiency, thermal stability, and full width at half maximum), all performance characteristics can be comprehensively considered to obtain the optimal doping range.

[0033] The process generally involves first determining the preset concentration ranges of the dopant and charge compensation agent (such as LiF), and then designing and preparing multiple formulations using orthogonal arrays (such as L9, L16, etc.). The resulting samples are then tested for performance parameters such as luminescence efficiency. Through methods such as normalization, weighted scoring, main effect analysis, and interaction analysis, the concentration combination with the optimal comprehensive score is selected. This step significantly improves the efficiency of process screening and ensures the accuracy and repeatability of doping concentration determination through scientific statistics, effectively improving the luminescence performance of the product and the stability of the process.

[0034] S3. Mix the target raw materials according to the target doping ratio to obtain a uniformly mixed premix. Premixes refer to homogeneous mixtures obtained by mixing target raw materials with optimized doping concentrations in a specific ratio. The core requirement is that the components are evenly distributed, without local enrichment or agglomeration, ensuring that the dopant can uniformly enter the crystal lattice.

[0035] The purpose of this step is to ensure that each raw material can fully participate in the subsequent reaction by thoroughly mixing the different components, preventing problems such as local defects, component segregation or incomplete reaction caused by uneven mixing, thereby improving the luminescence consistency and batch stability of the phosphor.

[0036] Mechanical mixing is typically achieved using planetary ball mills or high-shear mixers. By setting the milling time (e.g., 2 hours), rotation speed (e.g., 300 rpm), media (e.g., zirconia balls), and atmosphere (e.g., inert gas), fine particle size dispersion and composition homogenization are fully realized. Some processes also incorporate ultrasonic treatment or solvent-assisted dispersion to further enhance uniformity. This premixed material not only improves the reactivity of subsequent heat treatment but also ensures the effective incorporation rate of dopants and compensators during crystal growth, thereby improving the quality and batch consistency of the final product.

[0037] S4. Heat-treat the premixed material under a reducing atmosphere according to a preset temperature range to obtain heat-treated material; Heat treatment refers to the high-temperature reaction of premixed materials under a specific temperature and atmosphere, allowing dopants to effectively enter the main crystal lattice and complete crystal growth. Here, the reducing atmosphere refers to an atmosphere with low oxygen partial pressure or containing a small amount of reducing gas (such as an argon-hydrogen mixture), used to prevent valence state changes of sensitive ions, thereby promoting complete crystal growth, effective solid solution of dopant ions, and reducing the formation of crystal defects or impurity phases. Properly controlling the heat treatment temperature, atmosphere, and holding time can maximize crystallinity and doping efficiency.

[0038] The specific implementation of heat treatment typically involves: loading a uniformly mixed premix into a high-purity alumina crucible, placing it in a tube furnace or box furnace, setting the heating rate, heating to the target temperature and holding it at that temperature for several hours, followed by slow cooling to room temperature. The reducing atmosphere consists of high-purity argon and a small amount of hydrogen (e.g., a 95:5 volume ratio). This heat treatment method not only avoids redox anomalies in dopants but also effectively reduces vacancy defects and disordered phases in the material, improving the luminescence efficiency and thermal stability of the phosphor.

[0039] S5. The heat-treated material is crushed and sieved to obtain the narrow-band fluoride phosphor.

[0040] Crushing and screening refers to the mechanical crushing and particle size screening of solid materials obtained after heat treatment, ultimately yielding narrow-band fluoride phosphors with suitable particle size and uniform distribution. Typical particle sizes include D50 = 3~5 μm.

[0041] The purpose of this step is to transform the large, agglomerated solids obtained from heat treatment into micron-sized powders that are easy to encapsulate and apply, while removing excessively large or fine impurity particles, so that the product particle size is controlled within the range most suitable for luminescence and coating, thereby improving its dispersibility and application performance.

[0042] Crushing can be performed using equipment such as planetary ball mills, air jet mills, or vibratory mills, while sieving can be carried out using standard sieves (e.g., 300-500 mesh) for multi-stage separation. Some processes also combine wet classification or air jet classification to obtain a narrower particle size distribution. This treatment not only improves the light scattering uniformity and mixing properties of the phosphor but also facilitates subsequent surface coating, dispersion, and encapsulation, contributing to high color purity, high efficiency, and stable luminescence performance in the final device.

[0043] Preferably, obtaining the target doping concentrations of the dopant and charge compensator based on orthogonal experimental design and a preset doping concentration range includes: S21. Based on the preset doping concentration range of the dopant and the charge compensation agent, select multiple concentration levels and combine them to obtain an orthogonal experimental factor table; The preset doping concentration ranges for dopants and charge compensators in this step refer to the concentration variation ranges that may bring better performance to each factor, based on previous literature research, practical experience, or preliminary experimental results.

[0044] The purpose of this step is to achieve systematic coverage of the experimental design space through reasonable factor and level settings, ensuring that the main concentration ranges are not missed, while effectively reducing the workload and screening blind spots.

[0045] In practice, firstly, several representative concentration levels (such as low, medium, and high) are selected for each factor. Then, orthogonal arrays (such as L9, L16, etc.) are used to arrange and combine multiple factors at multiple levels, ultimately obtaining an orthogonal experimental factor table. This table serves as the basis for subsequent experimental formulations, efficiently screening out the optimal concentration combination and ensuring that the synergistic effect of multiple factors is fully reflected. This design greatly improves experimental efficiency and is conducive to fully exploring the luminescence performance potential of the doped system. S22. Based on the orthogonal experimental factor table, multiple sets of experimental formulations to be prepared are obtained; The experimental formulation group refers to the specific chemical ratio schemes corresponding to each group in the orthogonal experimental factor table. Each formulation group is a set of dopant / charge compensator concentration combinations to be experimentally verified.

[0046] The purpose of this step is to translate the experimental design into specific and executable chemical formulations, facilitating subsequent batch preparation and comparative analysis. Based on the factor table designed in S21, the corresponding ingredient schemes for all groups are listed, forming a clear list of experimental formulations. For example, rather than limiting it, Group 1 consists of 0.3 mol% Mn4+, 0.5 mol% Yb3+, and 0.1 mol% Li+; Group 2 consists of 0.5 mol% Mn4+, 1.0 mol% Yb3+, and 0.2 mol% Li+, and so on. Each group clearly indicates the amount of each raw material and the required purity. This ensures the systematic nature and traceability of subsequent preparations and facilitates data processing and result tracking.

[0047] S23. Prepare the phosphor according to the preset preparation parameters and the experimental formula group to obtain the corresponding phosphor sample; The preset preparation parameters include a series of process conditions that affect product performance, such as raw material ball milling time, mixing temperature, heat treatment temperature / time, and reducing atmosphere composition. The phosphor sample refers to the finished powder prepared according to each experimental formulation and process parameter, with the performance to be tested.

[0048] The purpose of this step is to control the consistency of other non-variable conditions to the greatest extent possible, so that the performance differences of each group of phosphors are mainly attributed to the ratio of dopant / compensator, thereby ensuring the scientific nature and accuracy of the screening results.

[0049] In practice, following the S22 formulation scheme, each raw material was accurately weighed, ball-milled, mixed, and placed in a crucible. The reaction was completed under uniform heat treatment temperature, atmosphere, and holding time. Afterward, the mixture was cooled, crushed, and sieved to obtain powder samples with the target particle size distribution. Strict process control ensured the comparability between samples and the validity of the experimental data.

[0050] S24. The performance of the phosphor samples is tested respectively to obtain the luminescence performance parameters of each phosphor sample; Luminescence performance parameters typically include quantum efficiency, luminescence intensity, full width at half maximum (FWHM), thermal stability, and chromaticity coordinates. The purpose of this step is to quantitatively and systematically evaluate the practical application performance of each phosphor group, providing crucial data support for subsequent formulation optimization and mechanism analysis.

[0051] In the implementation process, standard instruments such as spectrophotometers, integrating spheres, and spectral analyzers were used to measure the excitation / emission spectra, quantum efficiency, and luminescence retention rate at temperature rise for each group of samples. Some indicators (such as color purity) could be further quantified using CIE chromaticity coordinates. After data acquisition, multi-component comparisons and records were performed. This process ensured the scientific validity of subsequent parameter normalization and multi-objective weighted scoring, and provided high-quality raw data for subsequent steps such as orthogonal screening and response surface methodology.

[0052] S25. Perform correlation analysis on the luminescence performance parameters and experimental formulation group corresponding to each phosphor sample to obtain the target doping concentration of dopant and charge compensator.

[0053] Correlation analysis refers to the systematic statistical comparison of the performance parameters of each phosphor sample with its experimental formulation, using methods such as multi-objective weighted scoring, main effect analysis, and interaction analysis. The target doping concentration is the optimal ratio range or specific value for the final performance.

[0054] The purpose of this step is to scientifically determine the optimal doping concentration of dopant and compensator based on large sample performance data and through quantitative analysis methods, so as to maximize the material performance.

[0055] In practice, the process begins by pre-setting weights for each performance parameter and normalizing the results to obtain a weighted score for each formulation. Then, single-factor (main effect) analysis is used to determine the optimal concentration range for each element. Further multi-factor (interaction) analysis is then combined to screen for the optimal doping concentration combination that achieves the best multi-objective performance and synergistic effect. Finally, the screening results are back-referenced to the preparation parameter table to determine the optimal formulation suitable for industrial scale-up. This analytical strategy avoids the biases caused by single-index optimization, taking into account multiple properties such as luminous efficiency, thermal stability, and color purity, effectively ensuring the material's application effectiveness and promotional value in high-end LED lighting and other scenarios.

[0056] Preferably, the step of selecting multiple sets of doping concentration levels according to the preset doping concentration ranges of the dopant and the charge compensator to obtain an orthogonal experimental factor table includes: S211. Based on the preset doping concentration range of the dopant and the charge compensator, perform concentration range segmentation to obtain the effective concentration range of the dopant and the charge compensator; Specifically, the preset doping concentration ranges for dopants and charge compensators in this step refer to the reasonable concentration variation ranges set for each dopant and charge compensator based on previous process experience, literature data, or preliminary performance tests. The effective concentration range is the actual usable concentration range remaining after removing unsuitable extreme concentrations, such as those prone to concentration quenching or side reactions. By reasonably segmenting the range, the experimental design scope is narrowed, and theoretically or empirically unsuitable ranges are eliminated, thereby improving the efficiency and targeting of subsequent screening. Historical data and rapid small-sample test results can be combined to segment the initial concentration range, eliminating ranges that may lead to abnormal performance and retaining only the concentration range with luminescent performance potential. This reduces the amount of subsequent experiments and significantly increases the probability of obtaining a high-quality formulation.

[0057] S212. Based on the effective concentration range, perform a concentration sensitivity assessment to obtain the high-sensitivity and low-sensitivity segments of the dopant and the charge compensator; Concentration sensitivity assessment refers to analyzing the sensitivity of dopants and charge compensators to changes in target performance (such as luminous efficiency, thermal stability, etc.) in different concentration ranges, distinguishing between high-sensitivity ranges (ranges where performance fluctuates significantly with small changes in concentration) and low-sensitivity ranges (ranges where performance changes gradually with concentration).

[0058] The purpose of this step is to achieve precise allocation of experimental resources: for highly sensitive sections, denser experimental points are used to meticulously depict the details of performance changes; for low-sensitive sections, point selection can be simplified, saving experimental costs and manpower.

[0059] In practice, rapid preliminary experiments, historical data analysis, or simulated curves can be used to calculate the performance slope or variance within each concentration range, distinguishing between high-sensitivity and low-sensitivity regions. This allows for the precise identification of potential optimal ranges, improving the scientific rigor of the data and the reliability of the conclusions.

[0060] S213. Divide the high-sensitivity region into non-equidistant segments and the low-sensitivity region into equidistant segments to obtain a set of concentration levels of the dopant and the charge compensation agent. In this step, non-equidistant division refers to setting multiple experimental points with smaller concentration steps in the highly sensitive region, such as 0.30, 0.35, and 0.40 mol%, to finely cover performance changes; while in the low-sensitivity region, equidistant division is used, such as taking one point every 0.10 mol%, to simplify the experimental design. The concentration level set refers to summarizing all scientifically divided specific concentration points that can be used for experimental design. The purpose of this step is to balance experimental comprehensiveness and economy, ensuring that a limited number of experiments cover as much effective information as possible and avoiding omission of key performance points. Based on the sensitivity assessment results, the sampling density and step size for each region are determined, and the summaries form the final concentration level set. This effectively prevents experimental blind spots and improves the accuracy of process window determination.

[0061] S214. Calculate the theoretical energy transfer efficiency for each set of concentration levels to obtain the energy co-efficiency parameters of each set of concentration levels. Theoretical energy transfer efficiency refers to the estimation of energy transfer efficiency of a material system under different dopant / compensator combinations. For example, the energy synergy efficiency parameters under different ratios can be predicted using Judd-Ofelt theory and the Förster resonance energy transfer model. The purpose of this step is to preliminarily screen out combinations with low energy transfer efficiency and poor synergy using theoretical methods, focusing the experimental emphasis on schemes with high theoretical predictions, thereby improving the success rate of subsequent experiments. In practice, a concentration-energy transfer efficiency calculation relationship can be established, and batch calculations can be performed for each concentration level set. The energy synergy efficiency parameter serves as a direct reference indicator for subsequent screening, helping to deeply integrate experimental design with material mechanisms and enhancing the scientific rigor of research.

[0062] For example, the theoretical energy transfer efficiency is calculated using the Förster formula, as shown below: In the formula, E is the theoretical energy transfer efficiency, and R is Mn. 4+ Yb 3+ The interionic spacing between the ions is represented by the displacement R0, a characteristic value of the SrF2 matrix. In this example, R0 is 0.8 nm.

[0063] S215. The energy synergy efficiency parameters are screened according to a preset threshold to obtain an effective concentration level combination that meets the preset energy transfer requirements. The screening of energy synergy efficiency parameters involves comparing the efficiency parameters of all concentration combinations obtained in the previous step with a preset threshold (such as 0.75 or 0.8). Combinations below this threshold are eliminated, retaining only those above the threshold that theoretically promise excellent energy transfer and luminescence efficiency. The purpose of this step is to further compress the experimental space, ensuring that the combinations entering the orthogonal experimental design possess highly efficient synergistic effects at the microscopic energy mechanism level. This can be achieved using batch screening algorithms or manual interpretation to eliminate all low synergy parameter points. This further improves the effectiveness and resource utilization of subsequent experiments, maximizing the success rate of innovative luminescent materials.

[0064] S216. Obtain the orthogonal experimental factor table based on the effective concentration level combination and the preset orthogonal experimental table type.

[0065] Orthogonal experimental factor tables are the foundational data tables for multi-factor experimental designs. The type of orthogonal experimental table (such as L9, L16, L25, etc.) is determined by the number of factors and levels. The purpose of this step is to use statistical experimental design methods to arrange the screened effective concentration levels into an orthogonal experimental plan, achieving scientific system coverage of multi-factor and multi-level combinations while significantly reducing experimental workload. Specifically, based on the final number of concentration level combinations, the most suitable orthogonal table type is selected, and statistical software automatically generates the orthogonal factor table. This ensures the scientific rigor and comprehensiveness of the experimental design and lays a solid foundation for subsequent high-throughput preparation and system performance optimization.

[0066] Preferably, the step of performing correlation analysis between the luminescence performance parameters and experimental formulation groups corresponding to each phosphor sample to obtain the target doping concentrations of the dopant and charge compensator includes: S251. Normalize the luminescence performance parameters of each phosphor sample according to the preset weights to obtain the weighted score of the experimental formula corresponding to each phosphor sample. The luminescence performance parameters include luminescence efficiency, full width at half maximum (FWHM), and thermal stability. The luminescence performance parameters in this step refer to several key indicators characterizing the luminescence properties and stability of phosphors, commonly including luminescence efficiency, full width at half maximum (FWHM), and thermal stability, such as efficiency decay rate at high temperatures. Weighted scoring refers to the comprehensive performance evaluation value obtained by normalizing and summing these parameters after assigning weights according to actual application requirements. Unifying performance indicators with different dimensions and different focuses into a quantitatively comparable scoring system facilitates subsequent multi-objective comprehensive optimization and selection.

[0067] First, the luminous efficiency, half-width at half-maximum (HWHM), and thermal stability of each sample are normalized. Then, a weighted comprehensive score is calculated based on the weights set by the user or application scenario (e.g., luminous efficiency 0.5, HWHM 0.3, thermal stability 0.2). This approach highlights the relative importance of different performance characteristics and provides an intuitive data foundation for multi-objective optimization of complex systems. This method effectively balances various performance indicators and improves the practical applicability of the screening results.

[0068] S252. Based on the weighted score and the preset score threshold, all experimental formulas are screened to obtain a group of candidate experimental formulas with a weighted score higher than the threshold. The preset scoring threshold refers to the minimum overall performance threshold set to ensure the practical usability and advanced nature of the phosphor. The candidate experimental formulation group is the set of all formulations with an overall score higher than this threshold. Based on the weighted scoring of multiple performance parameters, experimental formulations with poor performance or that do not meet application requirements are excluded, and only combinations with excellent performance that are worth further analysis are retained.

[0069] In practice, the weighted scores of all experimental formulations are compared with a scoring threshold, retaining only samples that exceed the threshold and automatically discarding substandard formulations. This not only ensures the validity of subsequent analyses but also improves the efficiency of R&D resource utilization.

[0070] S253. Based on the dopant concentration levels in the candidate experimental formulations, the weighted average score corresponding to each dopant concentration level is calculated to obtain the main effect weighted score distribution for different dopant concentration levels. The main effect weighted score distribution refers to the weighted average score of all candidate formulations at different dopant concentration levels, with other factors fixed. This distribution can intuitively reflect the main influence trend of dopant concentration changes on performance. The optimal range of dopant concentration on luminescence performance is identified, providing a basis for determining the optimal dopant concentration.

[0071] In practice, candidate experimental formulations are grouped according to dopant concentration levels, and the weighted average score of each group is calculated. The results are displayed using line charts or bar charts, highlighting which concentration levels significantly improve overall performance. This allows for rapid identification of high-performance concentration ranges and reduces invalid experiments.

[0072] S254. Based on the concentration levels of each charge compensator in the candidate experimental formulation group, the weighted average score corresponding to each charge compensator concentration level is calculated to obtain the main effect weighted score distribution of different concentration levels of charge compensator. The definition of the main effect weighted score distribution here is similar to that in S253, but the object is different concentration levels of the charge compensator. The statistical method and purpose are completely consistent, namely, to explore the optimal range of charge compensator concentration. By comparing the weighted score mean at different charge compensator concentrations, the mechanism of action of the compensator on luminescence performance and the optimal addition amount can be clarified.

[0073] S255. Based on the main effect weighted score distribution of dopant and charge compensator, determine the concentration ranges where the weighted score improvement is most significant for dopant and charge compensator respectively, and denote them as the main effect concentration ranges. The main effect concentration range is the optimal range among the dopant and charge compensator concentration levels that significantly improves or maintains a high weighted score. This range will be the focus of subsequent in-depth analysis and orthogonal experiments. The purpose of this step is to directly derive the concentration range with the most significant performance improvement from the main effect analysis results, thereby achieving experimental focus and design optimization. In practice, the range near the maximum score value is usually considered the main effect range, but it can be appropriately relaxed based on actual process tolerances. This focus effectively compresses the subsequent experimental space, improves optimization efficiency, and enhances the relevance of the conclusions.

[0074] S256. Based on the main effect concentration range and the concentration combination of dopant and charge compensator in the candidate experimental formulation group and their weighted scores, perform interaction analysis to obtain the interaction analysis results. Interaction analysis examines the combined effects of different concentration combinations of dopants and charge compensators on weighted scores, determining whether synergistic enhancement or inhibition effects exist. This step aims to further optimize concentration combinations within the main effect concentration range, capturing synergistic advantages that single-factor analysis cannot reveal. Within the main effect range, a two-dimensional matrix is ​​constructed of all dopant-charge compensator concentration combinations and their corresponding weighted scores. The mean of the combined weighted scores is compared with the single-factor main effect scores to identify concentration combinations with significant synergistic enhancements. This step significantly raises the performance optimization ceiling of multi-component doped systems, laying the foundation for materials innovation.

[0075] S257. Based on the interaction analysis results, obtain the target doping concentrations of the dopant and charge compensator. The target doping concentrations in this step are the dopant and charge compensator concentration values ​​or concentration ranges that are ultimately selected through the aforementioned interaction analysis and have the best overall performance or best meet the application requirements.

[0076] The purpose of this step is to provide the optimal ratio that is highly consistent with theory and practice based on a systematic analysis of large samples, multiple parameters, and multiple methods, so as to maximize the performance of narrow-band fluoride phosphors.

[0077] Ultimately, by backtracking the interaction analysis matrix and finding the maximum score points or intervals, the optimal concentration scheme is determined and then experimentally verified or mass-produced. This method ensures the scientific rigor, advanced nature, and mass production feasibility of the formulation decision.

[0078] Preferably, the interaction analysis is performed based on the main effect concentration range and the concentration combinations of dopants and charge compensators in the candidate experimental formulation group, along with their weighted scores, to obtain the interaction analysis results, including: S2561. Based on the dopant and charge compensator concentration combination of the candidate experimental formulation group, grouping is performed within the main effect concentration range to obtain a combined group with the dopant concentration level as the row and the charge compensator concentration level as the column. Specifically, the combination grouping in this step refers to screening and grouping all combinations of dopant and charge compensator concentrations in the candidate experimental formulations within the aforementioned main effect concentration range (i.e., the optimal range determined through single-factor analysis). Different dopant concentrations are used as rows, and different charge compensator concentrations as columns, corresponding to different combinations. This focuses on effective combinations within the main effect range in the multi-parameter experimental space, significantly narrowing the scope of data analysis and enhancing the specificity and resolution of subsequent statistics.

[0079] The concentration points of all candidate experimental formulations were compared one by one, and only those combinations in which the concentrations of both factors were within the main effect range were retained. Then, a two-dimensional combination grouping table was generated in a row-column manner. This avoids accidental high scores caused by extreme parameters and ensures the robustness of the analytical conclusions and their relevance to practical applications.

[0080] S2562. Based on the above combination grouping, obtain the weighted score dataset corresponding to each combination of dopant concentration level and charge compensator concentration level. Specifically, the weighted scoring dataset in this step refers to the collection of weighted scoring data for all samples in the candidate experimental formulation group for each specific combination of dopant and charge compensator concentrations in S2561, forming a complete original dataset. For each two-dimensional combination unit, data points in all experimental formulations where the dopant and charge compensator concentrations are consistent with that combination are retrieved, and the weighted scores of these samples are extracted and categorized by combination number. This ensures that the scoring statistics for each combination are supported by actual samples, making the analysis results more scientific and representative.

[0081] S2563. Based on the weighted scoring dataset, calculate the average weighted score corresponding to each combination of dopant and charge compensator concentrations to obtain the average weighted score matrix of each combination. The average weighted score matrix in this step refers to the mean of the weighted score calculated for each combination dataset obtained from S2562. All means are arranged in a row-column fashion to form a two-dimensional matrix. The purpose of this step is to quantitatively reflect the synergistic effect of different concentration combinations on the overall performance of phosphors and to lay an intuitive data foundation for interaction analysis. This matrix can intuitively show which concentration combinations achieve "superimposed" performance improvement or "mutually exclusive" performance degradation, greatly facilitating subsequent determination of the optimal combination and process promotion.

[0082] S2564. Based on the single-factor average weighted score distribution corresponding to the concentration levels of each dopant in the candidate experimental formulation group, and the single-factor average weighted score distribution corresponding to the concentration levels of each charge compensator, a comparative processing is performed to obtain the scoring reference benchmark. For each dopant concentration level and each charge compensator concentration level within the main effect range, the weighted average score was calculated across all candidate formulations to obtain a one-dimensional single-factor score distribution. This quantifies the individual contribution at each level, providing a reference line for subsequent comparisons.

[0083] S2565. Based on the scoring reference benchmark and the average weighted scoring matrix of each combination, obtain the interaction analysis matrix of each dopant and charge compensator concentration combination; The interaction analysis matrix in this step is calculated by comparing the combined average weighted score matrix obtained in S2563 with the single-factor score reference benchmark in S2564, thus determining the actual improvement or suppression value for each combination (e.g., "Combination Score - Reference Benchmark"). For each cell in the matrix, its score is compared with the corresponding row / column single-factor benchmark to calculate the improvement or difference, forming an analysis matrix that reflects the strength and distribution of the interaction. This method clearly displays the combination points and intervals with the most significant performance synergy.

[0084] S2566. Based on the interaction analysis matrix and the scoring reference benchmark, a significance judgment is made to obtain the interaction analysis results.

[0085] In this step, the interaction analysis matrix obtained in S2565 is screened using statistical significance criteria (such as being greater than a certain threshold of the mean or exceeding the standard deviation), and the final output is the synergistic enhancement or optimal combination with statistical significance as the interaction analysis result.

[0086] A significant improvement threshold can be set using t-tests, z-score methods, or empirical criteria, retaining only combinations that are significantly higher than the reference baseline. Ultimately, one or more target concentration ranges / points are output, providing authoritative and systematic data for actual formulation development or product scale-up.

[0087] Preferably, the step of heat-treating the premixed material under a reducing atmosphere within a preset temperature range to obtain a heat-treated material includes: S41. The premixed material is heated to a target temperature in the preset reducing atmosphere according to a preset heating rate, wherein the reducing atmosphere is a mixed gas including hydrogen and argon, the mixing ratio of hydrogen and argon in the mixed gas is 95:5, and the target temperature is between 1100℃ and 1300℃. The reducing atmosphere in this step refers to the mixed gas used to control the redox properties of the reaction atmosphere, typically consisting of hydrogen (…). It consists of hydrogen (Hydrogen) and argon (Ar). Hydrogen has good reducing power and can effectively inhibit the excessive oxidation of metal ions, while argon is an inert gas that provides protection. The heating rate and target temperature refer to the energy required to heat the reaction system to a set temperature (e.g., 1100℃~1300℃) at a specified rate to achieve the physical or chemical reaction.

[0088] The purpose of this step is to ensure that the dopant can effectively enter the matrix lattice under high temperature conditions and to control its valence state and reaction environment, avoiding the formation of impurity phases or low-valence ions. A reasonable hydrogen / argon ratio (95:5) helps maintain a strong reducing environment, stabilizes the atmosphere, and reduces unnecessary side reactions.

[0089] The uniformly milled premixed material is placed in a high-temperature reactor, and a mixture with a volume ratio of 95:5 is introduced. Using a mixed Ar gas, a heating rate (e.g., 3-5℃ / min) is set, and the system is slowly heated to the target temperature of 1100℃~1300℃. By precisely controlling the atmosphere and temperature, the activation and doping of dopants are maximized, while the formation of harmful impurity phases is suppressed, thereby improving the crystallinity and uniformity of the material.

[0090] S42. According to the vapor deposition method, the vapor phase component is deposited at the target temperature to cause a lattice-oriented crystallization reaction; Vapor deposition is a high-temperature process in which precursor components of a material are deposited in gaseous form in a high-temperature region, where they undergo a deposition reaction on the surface of a substrate or the inner wall of a reactor to form solid crystals. Lattice-oriented crystallization refers to the orderly growth of crystals along specific orientations or lattice planes under external induction, thereby obtaining materials with high crystallinity and few defects.

[0091] The purpose of this step is to promote the rapid nucleation and orderly growth of fluoride materials through a gas-solid process, so as to achieve uniform entry of dopants into the crystal lattice and obtain ideal particle size and morphology, thereby improving the optical performance of the material.

[0092] In practice, at the target temperature, volatile or vaporized components such as fluorides and dopants are redeposited in the reaction zone, undergoing ordered crystallization under thermodynamic and external field induction. By adjusting the reaction atmosphere, temperature, and substrate surface conditions, directional growth is promoted, forming fluoride crystals with high specific surface area and high crystallinity. This process can significantly improve the density and uniformity of the material, providing a solid structural foundation for subsequent luminescent properties.

[0093] S43. Maintain the deposition reaction temperature and reducing atmosphere according to the preset holding time to form fluoride crystal particles with a target average specific surface area, wherein the preset holding time is 2-4 hours, and the target average specific surface area is 3 μm. 2 / g~5m 2 Between / g; the holding time refers to the duration of the reaction under the target temperature and atmosphere conditions (2~4 hours); specific surface area is the total surface area per gram of powder, usually expressed in m² / g. A higher specific surface area means smaller particle size or a rougher surface, which is beneficial for enhancing the interfacial interaction between the material and the external environment, such as the encapsulating adhesive, and improving the efficiency of light scattering and emission.

[0094] The purpose of this step is to allow the vapor deposition reaction to proceed fully, so that the crystal structure is completely formed and the dopant is evenly distributed. By precisely controlling the holding time and reducing atmosphere, the target specific surface area of ​​the fluoride crystal particles can be achieved.

[0095] The process involves maintaining the target temperature for 2-4 hours after vapor deposition and directional crystallization to ensure complete reaction, sufficient crystal growth, and that the particle size and surface structure reach the set range (e.g., 3-5 m² / g). Appropriate temperature control can achieve higher crystallinity, better particle distribution, and higher specific surface area, resulting in stronger luminescent properties and material dispersibility.

[0096] S44. Cool the fluoride crystal particles to room temperature according to a preset cooling rate to obtain the heat-treated material, wherein the preset cooling rate is less than or equal to 2°C / min.

[0097] Cooling rate refers to the speed at which a reaction system cools from a high temperature to room temperature, typically less than or equal to 2°C / min. Slow cooling helps release internal stress and stabilize the structure of the crystal, avoiding defects such as microcracks, internal stress, or secondary phase precipitation caused by sudden cooling.

[0098] The purpose of this step is to stabilize the crystal structure, reduce residual stress, and ultimately obtain heat-treated materials with balanced physical and chemical properties.

[0099] In practice, after the heating device is turned off, the reaction system is slowly cooled to room temperature at a preset cooling rate, allowing the crystal particles to spontaneously align and lock into their ideal structure during the cooling process. Slow cooling also effectively prevents material damage or surface oxidation caused by drastic temperature changes, improving the batch stability of the phosphor and the consistency of subsequent applications.

[0100] Preferably, the step of crushing and sieving the heat-treated material to obtain the narrow-band fluoride phosphor includes: S51. Place the heat-treated material in a planetary ball mill and grind it according to a preset rotation speed and preset ball milling time to obtain pulverized material. Planetary ball mills are highly efficient equipment for pulverizing and homogenizing materials, characterized by uniform energy distribution and precise particle size control. The preset rotation speed (e.g., 300 rpm) and preset milling time (e.g., 2 hours) are optimal process parameters selected based on the material's physical properties and the desired crushing outcome. The pulverized material refers to the granular powder obtained after ball milling. During the ball milling process, the material repeatedly collides and shears between the high-speed rotating mill and the grinding balls, ultimately forming a uniform powder without large agglomerations. This method effectively reduces the particle size of raw materials, improves the controllability of subsequent processes, and enhances product consistency.

[0101] S52. The pulverized material is sieved according to the target particle size range to obtain the narrow-band fluoride phosphor, wherein the preset rotation speed is 300 rpm, the preset ball milling time is 2 h, and the target particle size distribution range is 8~12 μm; Specifically, the pulverized material is poured into multi-stage standard sieves (such as 300 mesh and 500 mesh), and particles with a diameter controlled within 8~12μm are collected as the product through mechanical vibration or air classification. The remaining particles can be recycled and pulverized again. The narrow-band fluoride phosphor obtained after this process has excellent particle size uniformity and dispersibility, which is beneficial for subsequent surface coating, encapsulation, and practical lighting applications, improving the overall performance and stability of the device.

[0102] Preferably, after sieving the pulverized material according to the target particle size range to obtain the narrow-band fluoride phosphor, the method further includes: S53. Tetraethoxysilane was used as a precursor and dissolved and mixed in ethanol:deionized water:ammonia water at a volume ratio of 4:1:0.1. The mixture was then subjected to a hydrolysis reaction to obtain a stable silica sol. Tetraethoxysilane (TEOS) used in this step is a commonly used silicon precursor that readily hydrolyzes to form silica. Ethanol is used as the organic solvent, deionized water provides the source for the hydrolysis reaction, and ammonia acts as a catalyst to promote the hydrolysis and condensation of TEOS. A volume ratio of 4:1:0.1 helps control the reaction rate and particle size distribution, resulting in a highly dispersible and stable silica sol.

[0103] S54. Using ultrasonic vibration or mechanical stirring, the narrow-band fluoride phosphor is uniformly dispersed in the silica sol to form a phosphor suspension; Ultrasonic vibration or mechanical stirring in this step are two common dispersion methods that can effectively break up powder agglomerates and ensure their uniform distribution within the sol. A phosphor suspension refers to a reaction mixture in which narrow-band fluoride phosphor particles are uniformly distributed within a silica sol system after dispersion treatment.

[0104] The purpose of this step is to fully expose the phosphor particles within the silica sol, enabling subsequent... The uniformity and integrity of the coating improve the dispersion and interfacial compatibility of the material.

[0105] In practice, phosphors of the target particle size are added to the prepared silica sol and thoroughly dispersed using ultrasound (e.g., 30 min, 40 kHz) or high-speed stirring (e.g., 1000 rpm, 30 min). This significantly reduces particle agglomeration, enhances the subsequent coating effect, and lays the foundation for a dense and uniform coating layer.

[0106] S55. Heat the phosphor suspension to 60°C and react at a constant temperature for 2 hours to generate a silica coating layer with an average thickness of a preset value on the phosphor surface in situ using tetraethoxysilane. Heating to 60°C and maintaining this temperature for 2 hours is an optimized sol-gel reaction condition, which allows tetraethoxysilane to hydrolyze and condense on the phosphor surface, resulting in the in-situ growth of a silica coating layer with an average thickness of a preset value (e.g., 3-10 nm). The thickness of this coating layer can be adjusted to meet the interface performance requirements of different applications.

[0107] The dispersed phosphor suspension was heated to 60°C and stirred at this temperature for 2 hours. During the reaction, tetraethoxysilane hydrolyzed to produce... , and then condense into Ultimately, a uniform coating layer is deposited on the phosphor surface. Appropriate reaction time and temperature ensure that the coating layer is dense and does not clog the interparticle spaces, thus contributing to improved final performance.

[0108] S56. The product after the reaction is washed and dried to obtain a surface coating. Narrow-band fluoride phosphor in layers.

[0109] After the reaction, the precipitate is separated by centrifugation or allowed to stand, and then repeatedly washed with deionized water and ethanol until the washing solution is clear and neutral. Finally, it is dried in an oven. This process results in a final product with excellent dispersibility and environmental stability, effectively improving the lifespan, reliability, and luminous efficiency of the phosphor in practical LED or display applications.

[0110] Example 2 See also Figure 2 This invention also provides a method for encapsulating narrow-band fluoride phosphors, characterized in that the narrow-band fluoride phosphors are obtained by the method described in Example 1, the method comprising: S01. Obtain the target refractive index based on the refractive index of the narrow-band fluoride phosphor, wherein the target refractive index is between 1.6 and 1.7; The refractive index in this step refers to the physical parameter that affects the speed of light propagation and determines the optical matching of the phosphor-encapsulation material interface. For narrow-band fluoride phosphors, the refractive index is usually between 1.6 and 1.7, and the specific value can be obtained through literature review, material testing (such as ellipsometer measurement), etc.

[0111] The purpose of this step is to provide a scientific basis for the selection of subsequent encapsulation materials, reduce interface reflection loss by accurately matching the refractive index, and improve the light extraction efficiency of photons from the phosphor to the outside.

[0112] The theoretical refractive index can be calculated first based on the composition of the prepared phosphor, and then fine-tuned through actual measurements to finally lock in the target refractive index range. A scientific selection of the refractive index contributes to the efficient integration and performance maximization of the overall light-emitting device.

[0113] S02. Obtain the corresponding encapsulating adhesive according to the target refractive index, wherein the encapsulating adhesive includes hydrophobic phenyl silicone resin and a thermally conductive filler, the thermally conductive filler being AlN, and the water and oxygen permeability of the cured encapsulating adhesive is less than 5 × 10⁻⁶. -3 g·m -2 ·day -1 ; Encapsulating adhesives are transparent organic or inorganic colloidal materials commonly used in LED and phosphor encapsulation. Their main function is to firmly bond the phosphor to the excitation light source and protect it from external environmental influences. The purpose of this step is to select an encapsulating adhesive from commercially available materials such as silicone and epoxy resins with a refractive index matching the phosphor (1.6~1.7) based on the previously determined target refractive index, thereby optimizing the optical path design and reducing multi-interface reflection losses.

[0114] The colloid is selected based on supplier data or actual test results, or its refractive index is adjusted by appropriate doping. This ensures consistent light output from the packaged device and also helps to uniformly disperse phosphor particles within the package, improving the overall consistency and stability of the product.

[0115] In one specific embodiment, the encapsulating adhesive is composed of hydrophobic phenyl silicone resin and thermally conductive filler AlN aluminum nitride. The hydrophobic phenyl silicone resin, as the matrix, effectively blocks environmental moisture and reduces the risk of water and oxygen erosion to the phosphor, ensuring long-term stable luminescence. AlN, as a thermally conductive filler (e.g., at an addition amount of 10 wt%), significantly improves the overall thermal conductivity of the encapsulating adhesive, helping to quickly dissipate heat from the chip and excitation area, preventing fluorescence efficiency decay caused by high temperatures.

[0116] The purpose of this step is to prepare an encapsulating adhesive that combines high transparency, high thermal conductivity, and high barrier properties through material compounding and parameter optimization, ensuring the long-term reliability and high efficiency of the light-emitting device. After optimization of the formulation and curing process, the water and oxygen permeability of the encapsulating adhesive after curing can be controlled to be less than 5 × 10⁻⁶. -3 g·m -2 ·day -1 It effectively delays phosphor aging, inhibits performance degradation caused by water and oxygen, and is suitable for high-end applications such as high-brightness, long-life LED lighting and backlighting.

[0117] S03, based on the Yb in the narrow-band fluoride phosphor 3+ The absorption peak is used to obtain the target excitation wavelength; Yb 3+ The absorption peak refers to Yb 3+ The strong absorption region of ions in the blue light band is the starting point of the energy transfer chain. The target excitation wavelength refers to the light source wavelength that best matches this absorption peak to ensure optimal energy transfer efficiency.

[0118] The purpose of this step is to pinpoint Yb by using spectroscopic measurements (such as UV-Vis absorption spectroscopy) in conjunction with literature or simulation results. 3+ The optimal absorption peak position is determined to identify the most suitable excitation source wavelength.

[0119] Specifically, this can be achieved by using a spectrophotometer to measure the absorption spectrum of the phosphor and finding Yb. 3+ The absorption band is typically at its maximum at 450 nm. Precisely selecting the target excitation wavelength enables optimal matching between the excitation source energy and the energy level structure of the luminescent material, thereby improving energy transfer efficiency and the overall luminous efficiency of the device.

[0120] S04. Based on the target excitation wavelength, obtain the corresponding blue LED light-emitting chip as the excitation light source; Blue LED chips are currently the most commonly used excitation source in solid-state lighting and display technologies, offering stable wavelength and high output efficiency. The purpose of this step is to select or customize the dominant emission wavelength and Yb from a wide range of LED chip specifications based on the target excitation wavelength determined in the previous step. 3+ Blue LED chips with highly matched absorption peaks (e.g., 450nm) ensure the highest excitation efficiency of the light-emitting device during operation.

[0121] S05. Based on the encapsulating adhesive and the blue LED light-emitting chip, a narrow-band fluoride phosphor is encapsulated to obtain the target light-emitting device.

[0122] Phosphor is uniformly mixed into an encapsulating colloid and then applied to the light-emitting area of ​​the LED chip using dispensing or potting methods. After vacuum degassing and curing, the final product is manufactured. This step not only ensures uniform phosphor excitation and stable light output but also improves the device's mechanical strength and environmental tolerance. The resulting light-emitting device significantly outperforms traditional solutions in terms of color purity, luminous efficacy, and lifespan, making it suitable for high-end lighting and display applications.

[0123] Preferably, the encapsulation of narrow-band fluoride phosphors with the encapsulating adhesive and the excitation light source to obtain the target light-emitting device includes: S051. Fix the blue LED light-emitting chip onto the pad of the chip carrier, wherein the chip carrier is provided with a copper-based heat sink; In this step, the blue LED chip is the core light source used to excite the phosphor to produce light. The chip carrier is usually a printed circuit board (PCB) or a ceramic support, used to support and conduct the chip current. The copper-based heat sink is placed below the chip carrier as a highly efficient heat-conducting material, which plays a role in quickly dissipating the heat generated during chip operation.

[0124] The purpose of this step is to securely solder the blue LED chip onto the chip carrier pads equipped with copper-based heat sinks, laying the foundation for subsequent packaging and device thermal management. A well-designed heat dissipation structure can effectively reduce the operating temperature of the chip and phosphor, suppress thermal quenching, and improve the device's luminous efficacy and stability.

[0125] S052. According to the preset ratio, the encapsulating adhesive and narrow-band fluoride phosphor are mixed to obtain phosphor colloid; The encapsulating adhesive used in this step is a highly transparent colloid that is optically matched to the phosphor, typically made of silicone or epoxy resin. The phosphor and encapsulating adhesive are thoroughly mixed according to a preset ratio (e.g., 1:10 or as set by process standards) to form a phosphor colloid. The preset ratio must ensure uniform phosphor distribution and appropriate concentration to obtain ideal light color and brightness.

[0126] The purpose of this step is to ensure the uniform dispersion of phosphor within the encapsulating compound, thereby guaranteeing the optical uniformity and luminescence consistency of the subsequent encapsulation layer. Too much or too little phosphor may lead to color deviation or reduced brightness in the device.

[0127] In practice, the phosphor and encapsulating adhesive can be weighed and mixed in a dust-free environment. The mixture should be thoroughly stirred using methods such as magnetic stirring, ultrasonication, or mechanical dispersion. If necessary, vacuum degassing should be performed to prevent defects such as air bubbles from forming in the subsequent device. This ensures that the phosphor particles are fully coupled with the excitation light, improving the final light extraction efficiency and color purity.

[0128] S053. The phosphor colloid is coated on the blue LED light-emitting chip and cured to obtain the target light-emitting device.

[0129] Phosphor colloid is precisely dotted onto the chip's light-emitting area and then cured by heating or ultraviolet light, resulting in a robust, transparent, and bubble-free encapsulation layer. This ultimately yields a dense, uniformly colored, and high-performance target light-emitting device. This process not only improves product performance and batch consistency but also facilitates large-scale applications in lighting, backlighting, and other fields.

[0130] In one embodiment, a packaged LED obtained by the luminous efficiency improvement method of Example 1, using narrow-band fluoride phosphor and other phosphors (such as β-SiAlON green phosphor, silicate yellow phosphor, and a small amount of blue light excitation enhancement powder compounded in a predetermined ratio), is combined with the packaging described in the example to obtain the packaged LED. Figure 3 The figure shows the measured emission spectrum of the LED device at 25 °C. Figure 4 The diagram shows the points where the chromaticity coordinates fall within the ANSI-4000 K ellipse under the same driving conditions. Specifically, the upper left corner of the report displays the measured emission spectrum of the packaged LED at 25°C, with a test wavelength range of 380–780 nm. The spectrum shows clear distributions of blue, green, yellow, and red light, with a prominent red emission peak in the 600–680 nm range, reflecting the high-efficiency emission characteristics of the narrow-band fluoride red phosphor. This red light enhancement helps improve the overall color rendering index and color gamut coverage of the light source, meeting the application requirements of wide color gamut, high color rendering LED lighting.

[0131] Based on spectral data, the measured chromaticity coordinates of the LED are x=0.3790, y=0.3834, located near the center of the ANSI 4000K ellipse, corresponding to a correlated color temperature of 4087K, a dominant wavelength of 576.9nm, and a color purity of 28.8%. The ratio of the three primary colors is R: 20.2%, G: 75.0%, and B: 4.8%, with a reasonable color distribution that enhances overall visual comfort. In terms of color rendering performance, the comprehensive color rendering index Ra is as high as 98.9, with all R1-R15 values ​​above 98. The TM30 parameters Rf is 95.6, Rg is 99.4, and TLCI also reaches 99, fully meeting the high color rendering requirements of professional-grade applications such as film and television, and medical applications. Regarding color stability, the measured SDCM is 2.2, indicating stable colorimetric points. This demonstrates a high degree of uniformity in the packaging process and powder ratio, with minimal batch-to-batch color difference, meeting the standards for high-consistency lighting applications.

[0132] In terms of luminous and electrical performance, this LED delivers a luminous flux of 12.84 lm at a power of 45.45 mW, achieving a luminous efficacy of 157.17 lm / W, demonstrating extremely high photoelectric conversion efficiency. The LED has a photosynthetically active radiant flux (PPF) of 0.204 μmol / s, a photosynthetically active radiant power (PRF) of 42.75 mW, and a photon flux efficiency (PPEF) of 2.49 μmol / s / W, making it suitable for both plant lighting and high-end indoor lighting applications. It has a forward voltage of 2.725V, a forward operating current of 29.98mA, and a power of 81.72mW. The packaging is reliable, the operation is stable, and the electrical performance indicators are excellent.

[0133] In summary, the LED devices prepared and composite-encapsulated by the method of this invention not only achieve excellent spectral structure and color rendering performance, but also have high luminous efficacy, high color temperature consistency and excellent stability, providing solid technical support for high-end displays, healthy lighting and special application scenarios.

[0134] It should be clarified that the present invention is not limited to the specific configurations and processes described above and shown in the figures. For the sake of brevity, detailed descriptions of known methods are omitted here. In the above embodiments, several specific steps are described and shown as examples. However, the method process of the present invention is not limited to the specific steps described and shown. Those skilled in the art can make various changes, modifications, and additions, or change the order of steps, after understanding the spirit of the present invention.

[0135] Those skilled in the art will understand that embodiments of the present invention can be provided as methods, systems, or computer program products. Therefore, the present invention can take the form of a completely hardware embodiment, a completely software embodiment, or an embodiment combining software and hardware aspects. Furthermore, the present invention can take the form of a computer program product embodied on one or more computer-usable storage media (including, but not limited to, disk storage, CD-ROM, optical storage, etc.) containing computer-usable program code.

[0136] This invention is described with reference to flowchart illustrations and / or block diagrams of methods, apparatus (systems), and computer program products according to embodiments of the invention. It will be understood that each block of the flowchart illustrations and / or block diagrams, and combinations of blocks in the flowchart illustrations and / or block diagrams, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, special-purpose computer, embedded processor, or other programmable data processing apparatus to produce a machine, such that the instructions, which execute via the processor of the computer or other programmable data processing apparatus, generate instructions for implementing the flowchart illustrations and / or block diagrams. Figure 1 a process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.

[0137] These computer program instructions may also be stored in a computer readable memory that can direct a computer or other programmable data processing device to work in a specific manner, so that the instructions stored in the computer readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 a process or multiple processes and / or boxes Figure 1 The function specified in one or more boxes.

[0138] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing the instructions executed on the computer or other programmable device for implementing the process. Figure 1 a process or multiple processes and / or boxes Figure 1 The steps of the function specified in one or more boxes.

[0139] It should also be noted that the exemplary embodiments mentioned in this invention describe methods or systems based on a series of steps or apparatus. However, this invention is not limited to the order of the steps described above; that is, the steps can be performed in the order mentioned in the embodiments, or in a different order, or several steps can be performed simultaneously.

[0140] The above description is merely a specific embodiment of the present invention. Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working processes of the systems, modules, and units described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here. It should be understood that the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the protection scope of the present invention.

Claims

1. A method for improving the luminous efficiency of narrow-band fluoride phosphors, characterized in that, The method includes: The initial raw materials are screened according to the preset purity requirements to obtain the target raw materials. The target raw materials include matrix materials, dopants and charge compensators. The matrix materials include SrF2 and CaF2, the dopants include MnF3 and YbF3, and the charge compensator includes LiF. Based on orthogonal experimental design and preset doping concentration ranges, the target doping concentrations of the dopant and charge compensator were obtained. Specifically, the preset doping concentration range for MnF3 was 0.5–2.0 mol%, for YbF3 it was 1.0–3.0 mol%, and for LiF it was 0.8–1.5 mol%. The target raw materials are mixed according to the target doping ratio to obtain a uniformly mixed premix. The premixed material is heat-treated in a reducing atmosphere according to a preset temperature range to obtain a heat-treated material. The heat-treated material is crushed and sieved to obtain the narrow-band fluoride phosphor.

2. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to claim 1, characterized in that, The step of obtaining the target doping concentrations of the dopant and charge compensator based on orthogonal experimental design and a preset doping concentration range includes: Based on the preset doping concentration ranges of the dopant and the charge compensation agent, multiple concentration levels are selected and combined to obtain an orthogonal experimental factor table; Based on the orthogonal experimental factor table, obtain multiple sets of experimental formulations to be prepared; The phosphor was prepared according to the preset preparation parameters and the experimental formulation group to obtain the corresponding phosphor samples; The performance of each phosphor sample was tested to obtain the luminescence performance parameters of each phosphor sample. Correlation analysis was performed on the luminescence performance parameters and experimental formulations corresponding to each phosphor sample to obtain the target doping concentrations of dopants and charge compensators.

3. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to claim 2, characterized in that, The method involves selecting multiple sets of doping concentration levels based on preset doping concentration ranges for the dopant and the charge compensator, and combining them to obtain an orthogonal experimental factor table, including: Based on the preset doping concentration range of the dopant and the charge compensator, the concentration range is segmented to obtain the effective concentration range of the dopant and the charge compensator; Concentration sensitivity is evaluated based on the effective concentration range to obtain the high-sensitivity and low-sensitivity segments of the dopant and the charge compensator; The high-sensitivity region is divided into non-equidistant sections and the low-sensitivity region is divided into equidistant sections to obtain a set of concentration levels for the dopant and the charge compensator. The theoretical energy transfer efficiency is calculated for each set of concentration levels to obtain the energy co-efficiency parameter of each set of concentration levels. The energy synergy efficiency parameters are filtered according to a preset threshold to obtain an effective concentration level combination that meets the preset energy transfer requirements; Based on the effective concentration level combination and the preset orthogonal experimental table type, obtain the orthogonal experimental factor table.

4. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to claim 2, characterized in that, The correlation analysis between the luminescence performance parameters and experimental formulation group corresponding to each phosphor sample to obtain the target doping concentration of the dopant and charge compensator includes: The luminescence performance parameters of each phosphor sample are normalized according to a preset weight to obtain a weighted score of the experimental formulation corresponding to each phosphor sample. The luminescence performance parameters include luminescence efficiency, full width at half maximum (FWHM), and thermal stability. Based on the weighted score and the preset score threshold, all experimental formulas are screened to obtain a group of candidate experimental formulas with a weighted score higher than the threshold. Based on the concentration levels of each dopant in the candidate experimental formulation group, the weighted average score corresponding to each dopant concentration level is calculated to obtain the main effect weighted score distribution of different dopant concentration levels; Based on the concentration levels of each charge compensator in the candidate experimental formulation group, the weighted average score corresponding to each charge compensator concentration level was calculated to obtain the main effect weighted score distribution of charge compensator at different concentration levels. Based on the main effect weighted score distribution of dopant and charge compensator, the concentration ranges with the most significant increase in weighted score for dopant and charge compensator are determined and denoted as the main effect concentration ranges. Based on the main effect concentration range and the concentration combination of dopant and charge compensator in the candidate experimental formulation group and their weighted scores, interaction analysis was performed to obtain the interaction analysis results. Based on the interaction analysis results, the target doping concentrations of the dopant and charge compensator are obtained.

5. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to claim 4, characterized in that, The interaction analysis is performed based on the main effect concentration range and the concentration combinations of dopants and charge compensators in the candidate experimental formulations, along with their weighted scores, to obtain the interaction analysis results, including: Based on the dopant and charge compensator concentration combinations of the candidate experimental formulations, grouping is performed within the main effect concentration range to obtain combined groupings with dopant concentration levels as rows and charge compensator concentration levels as columns; Based on the above combination grouping, the weighted score dataset corresponding to each combination of dopant concentration level and charge compensator concentration level is obtained; Based on the weighted scoring dataset, the average weighted score corresponding to each combination of dopant and charge compensator concentrations is calculated to obtain the average weighted score matrix of each combination. Based on the single-factor average weighted score distribution corresponding to each dopant concentration level in the candidate experimental formulation group, and the single-factor average weighted score distribution corresponding to each charge compensator concentration level, a comparative processing was performed to obtain the scoring reference benchmark. The interaction analysis matrix of each dopant and charge compensator concentration combination is obtained by comparing the scoring reference benchmark with the average weighted scoring matrix of each combination. The significance of the interaction analysis is determined based on the interaction analysis matrix and the scoring reference, and the interaction analysis results are obtained.

6. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to any one of claims 1-5, characterized in that, The process of heat-treating the premixed material under a reducing atmosphere within a preset temperature range to obtain a heat-treated material includes: According to a preset reducing atmosphere, the premixed material is heated to a target temperature according to a preset heating rate. The reducing atmosphere is a mixed gas including hydrogen and argon, wherein the mixing ratio of argon and hydrogen in the mixed gas is 95:5, and the target temperature is between 1100℃ and 1300℃. According to the vapor deposition method, the vapor phase component is deposited at the target temperature, and a lattice-oriented crystallization reaction occurs. The deposition reaction is maintained at a temperature and reducing atmosphere for a preset holding time to form fluoride crystal particles with a target average specific surface area. The preset holding time is 2-4 hours, and the target average specific surface area is 3 μm. 2 / g~5m 2 Between / g; The fluoride crystal particles are cooled to room temperature according to a preset cooling rate to obtain the heat-treated material, wherein the preset cooling rate is less than or equal to 2°C / min.

7. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to any one of claims 1-5, characterized in that, The process of crushing and sieving the heat-treated material to obtain the narrow-band fluoride phosphor includes: The heat-treated material is placed in a planetary ball mill and crushed by ball milling according to a preset rotation speed and preset ball milling time to obtain pulverized material. The pulverized material is sieved according to the target particle size range to obtain the narrow-band fluoride phosphor. The preset rotation speed is 300 rpm, the preset ball milling time is 2 h, and the target particle size distribution range is 8~12 μm.

8. The method for improving the luminous efficiency of narrow-band fluoride phosphor according to claim 7, characterized in that, After sieving the pulverized material according to the target particle size range to obtain the narrow-band fluoride phosphor, the process further includes: Tetraethoxysilane was used as a precursor and dissolved and mixed in ethanol:deionized water:ammonia water at a volume ratio of 4:1:0.

1. The mixture was then subjected to a hydrolysis reaction to obtain a stable silica sol. The narrow-band fluoride phosphor is uniformly dispersed in the silica sol by ultrasonic vibration or mechanical stirring to form a phosphor suspension; The phosphor suspension is heated to 60°C and kept at a constant temperature for 2 hours to generate a silica coating layer with an average thickness of a preset value on the phosphor surface in situ by tetraethoxysilane. The product after the reaction was washed and dried to obtain a narrow-band fluoride phosphor with a SiO2 coating on the surface.

9. A method for encapsulating narrow-band fluoride phosphors, characterized in that, The narrow-band fluoride phosphor is obtained by the method according to any one of claims 1-8, the method comprising: The target refractive index is obtained based on the refractive index of the narrow-band fluoride phosphor, wherein the target refractive index is between 1.6 and 1.

7. A corresponding encapsulating adhesive is obtained based on the target refractive index, wherein the encapsulating adhesive comprises a hydrophobic phenyl silicone resin and a thermally conductive filler, wherein the thermally conductive filler is AlN, and the water and oxygen permeability of the cured encapsulating adhesive is less than 5 × 10⁻⁶. -3 g·m -2 ·day -1 ; According to the Yb in the narrow-band fluoride phosphor 3+ The absorption peak is used to obtain the target excitation wavelength; Based on the target excitation wavelength, obtain the corresponding blue LED light-emitting chip as the excitation light source; Based on the encapsulating adhesive and the blue LED light-emitting chip, a narrow-band fluoride phosphor is encapsulated to obtain the target light-emitting device.

10. The encapsulation method for narrow-band fluoride phosphor according to claim 9, characterized in that, The process of encapsulating a narrow-band fluoride phosphor with the encapsulating adhesive and the excitation light source to obtain the target light-emitting device includes: A blue LED light-emitting chip is fixed on a pad on a chip carrier, wherein the chip carrier is provided with a copper-based heat sink; According to the preset ratio, the encapsulating adhesive and narrow-band fluoride phosphor are mixed to obtain phosphor colloid; The target light-emitting device is obtained by coating a blue LED chip with phosphor colloid and then curing it.